Foreign policy in the twenty-first century - Hill, Christopher, 1948-; Hill, Christopher, 1948- (UK: Palgrave, 2016)
"Substantially revising and updating the influential and widely used The Changing Politics of Foreign Policy, this retitled new edition provides both an introduction to, and a reassessment of, the nature of foreign policy in the light of changing political conditions, international and domestic"--
Machine generated contents note: -- 1. Foreign Policy in International Relations -- 2. The Politics of Foreign policy -- 3. The Actors: Taking Responsibility -- 4. Agents: Bureaucracy and the Proliferation of External Relations -- 5. Rationality in Foreign Policy -- 6. Implementation: Foreign Policy Practice and the Texture of Power -- 7. Foreign Policy in a multi-actor world -- 8. Transnational Reformulations -- 9. The Domestic Sources of Foreign Policy -- 10. Politics, Society and Foreign Policy -- 11. Foreign Policy and the Revival of The State.
First edition published under the title The Changing Politics of Foreign Policy in 2003.
Includes bibliographical references and index.
Keywords: International relations; International relations -- Psychological aspects; POLITICAL SCIENCE / International Relations / General; POLITICAL SCIENCE / Public Affairs & Administration; POLITICAL SCIENCE / General